Development of Augmented Reality-Based Mobile Learning Media on Molecular Shapes for High School Students - Zalukhu, Fandel Affection Christensen; Panggabean, Freddy Tua Musa (Jurnal Inovasi Pembelajaran Kimia, 2025)
Chemistry learning on molecular shapes remains challenging due to the abstract and three-dimensional nature of the concept, while existing learning media often fail to provide interactive visualization. This study aims to develop and evaluate an Augmented Reality (AR)-based mobile learning media to improve students’ understanding of molecular geometry. The research employed a Research and Development (R&D) approach using the ADDIE model through stages of analysis, design, development, implementation, and evaluation. The developed AR media visualizes 3D molecular models that can be manipulated via smartphones. Expert validation results indicated that the media was highly feasible, while student trials showed significant improvements in learning outcomes (N-Gain = 0.65) and motivation. The findings suggest that AR technology effectively supports the comprehension of abstract chemical concepts and offers an innovative solution for technology-integrated learning in 21st-century classrooms.